Optimalisasi Peran Kader Pos UKK Demang Jaya Sehat melalui Pemanfaatan Media Penyuluhan Kesehatan Sederhana - Eka Rosanti; Ratih Andhika Akbar Rahma; Mahmudah Hamawi; Dian Afif Arifah; Aisy Rahmania; Siti Ma'rifah (Warta LPM, 2024)
A program that has not been implemented at the Demang Jaya Sehat Post of Occupational Health Effort is village-level meetings as an effort to provide solutions to problems obtained when conducting introspective surveys. Currently, cadres are not able to carry out socialization because they have never received training related to socialization media. This service aims to provide simple health socialization media training to UKK Demang Jaya Sehat Post Cadres as a motor in the farmer health program. This service begins with a pretest, then simple socialization media training consisting of concepts, sources, and practices, and ends with a posttest. All 7 cadres were active and enthusiastic in participating in the training held at the Demangan Village Hall as seen from several questions asked. Cadres carry out the practice of searching for information and data using Google with keyword accuracy indicators, as well as accessing the website promkes.kemkes.go.id to download socialization media in the form of videos, short films, posters, brochures, flyers, and leaflets. Cadres are considered proficient in using gadgets. The posttest results showed an increase in cadre understanding scores of 20.75% compared to before. This shows that training activities are effective in increasing the knowledge of Pos UKK cadres so that they are expected to be able to maintain the sustainability of the village safety farming program. The lowest score is in the aspect of validity and accuracy of information, so farmers still need assistance from the community health center and village government team in preparing and conducting counseling.